Perceptions of didactic strategies among pupils and teachers in primary school - Mithans, Monika (CEPS journal, 2023)
The quality of educational work is inextricably linked to many factors at the system, school, teacher, and student levels. This research was carried out within the project ‘Education of Teachers as a Factor of Providing High-quality Life-long Learning in the Learning Society/The Society of Fast Socio-economic Changes and Unsure Future’, funded by the Slove-nian Research Agency. This paper provides a basic overview of the char-acteristics of open instruction, an umbrella term that combines active and learner-centred didactic strategies. The empirical section focuses on the use of didactic strategies. The survey was carried out with 1,536 primary school4 pupils in Grades 7 and 9 and 263 of their teachers. Both pupils and teachers cited problem-based learning and research-based learning as the most commonly used didactic strategies, while project-based learning was the least frequently used. Despite the agreement on the most and least frequently used didactic strategies, there are statisti-cally significant differences between pupils’ and teachers’ perceptions of all selected didactic strategies. Teachers reported that they used these strategies more often than was perceived by their pupils. We also found a statistically significant impact of better learning performance on the perception of certain didactic strategies. The results of the study raise new research questions, especially in the design of more detailed analy-ses of the use of didactic strategies in pedagogical practice.
Keywords: academic performance; aktivnost učencev; didactic strategies; osnovna šola; primary school; pupil activity; strategije pouka; učni uspeh